Sweet potato working group - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
All those working in sweet potato production or research will be interested in a new working group and the production of a newsletter on the subject. The International Working Group on Sweet Potato Virus (IWGSPV) aims to provide its members with an...